Literasi Digital Masyarakat Dalam Menghadapi Tantangan Digital Abad 21 Melalui Program Gerakan Literasi Digital di Kabupaten Garut - Siti Nurkamilah; Ejen Zaenal Muttaqin; Ahmad Sofwan (Jurnal Pengabdian Literasi Digital Indonesia, 2023)
Digital literacy is a competency that is needed by all elements of society. Digital literacy can help society in facing the digital challenges of the 21st century. Therefore, there is a need for special assistance to the public in understanding digital literacy as a whole both in aspects of digital skills, digital culture, digital ethics and digital security. The purpose of digital literacy assistance is to convey knowledge about the importance of understanding digital literacy in the community, the 4 pillars of digital literacy, stimulate the community in building a paradigm of the importance of digital security in facing the digital development of the 21st century, and be active in finding solutions to the digital literacy problems faced, as well as increasing public understanding of digital literacy after participating in mentoring activities. The partners of this mentoring activity are the Ministry of Communication and Information Technology of the Republic of Indonesia and Cibatu District, Garut Regency. The participants of this digital literacy assistance activity were 200 people in Cibatu-Garut District. This activity is carried out with expository and reflection methods. Community digital literacy activities through digital literacy seminars are public understanding of digital literacy related to digital literacy pillars, digital problems and their handling are increasing, this can be seen from the results of the community understanding questionnaire after participating in mentoring activities, namely 64.2% of people strongly agree and 33.8% agree with positive statements from digital literacy indicators. Then the community has begun to have a paradigm of the importance of digital security in facing digital developments in the 21st century, and is active in finding solutions to the digital literacy problems faced.